2019
DOI: 10.7717/peerj.6740
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive and degenerative evolution of theS-Phase Kinase-Associated Protein 1-Likefamily inArabidopsis thaliana

Abstract: Genome sequencing has uncovered tremendous sequence variation within and between species. In plants, in addition to large variations in genome size, a great deal of sequence polymorphism is also evident in several large multi-gene families, including those involved in the ubiquitin-26S proteasome protein degradation system. However, the biological function of this sequence variation is yet not clear. In this work, we explicitly demonstrated a single origin of retroposed Arabidopsis Skp1-Like (ASK) genes using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…For example, the list of E3 ligases encoded in the genome of Arabidopsis thaliana , a model plant, contains over 1300 members (Vierstra, 2009; Hua and Yu, 2019). The large expansion of the E3 ligase group is consistent with its roles in plant adaptation (Hua and Gao, 2019; Hua and Yu, 2019).…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…For example, the list of E3 ligases encoded in the genome of Arabidopsis thaliana , a model plant, contains over 1300 members (Vierstra, 2009; Hua and Yu, 2019). The large expansion of the E3 ligase group is consistent with its roles in plant adaptation (Hua and Gao, 2019; Hua and Yu, 2019).…”
Section: Introductionsupporting
confidence: 54%
“…Unfortunately, due to the varied effects of mutant alleles and their different genetic backgrounds ( axr6‐3 , cul1‐6 , and cul1‐7 are in Col‐0, icul3 is in Enkheim‐2 [En‐2], and cul‐494 is in Wassilewskija 4 [Ws‐4]), these mutants also showed several phenotypic differences, leaving the comprehensive functions of Cullin1 and SCF complexes unreconciled (Moon et al ., 2007; Gilkerson et al ., 2009; Pacurar et al ., 2014). Through genomic and evolutionary studies, we discovered that both FBX and ASK families showed significant sequence polymorphisms and diverse expression patterns across Arabidopsis populations, which indicates adaptive roles of SCF in different individuals (Hua et al ., 2013; Hua and Gao, 2019). Such natural variations further complicate the systematic understanding of SCF functions through mutagenesis analysis in different accessions.…”
Section: Introductionmentioning
confidence: 99%
“…Relaxed negative selection may indicate a trend of neutralization. To test this hypothesis, we examined the neutral evolution of a UPS gene using the same approach employed previously to identify neutral changes of the Arabidopsis Skp1-like (ASK) genes [41]. By comparing the likelihood ratio obtained from two runs of codeml program with both fixed and free K a / K s ratios from the PAML4 package [40], we identified in total 113 out of 987 UPS genes (11.4%) that are under neutral changes in Aly .…”
Section: Resultsmentioning
confidence: 99%
“…Tandem duplications and retrotranspostion have been found to play a key role in the recent expansion of the ASK ( Skp1 ) family in Ath and the Ubiquiton family in 50 plant genomes [18,41], both of which belong to the ubiquitylation system. We next asked whether these two duplication mechanisms have also contributed to the differential expansion and diverse selection patterns of the UPS gene families across Brassicaceae and Poaceae species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation